Examining the Loyalty of Diverse Internet Users and its Impact on Sports Public Relations - Bin Guo,; Maojun Zhou, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study explores the concept of user loyalty in the context of sports media consumption, particularly in relation to diverse internet users' engagement with online sports content. Building on the framework used for examining user stickiness in online variety shows, this paper develops and tests a model to identify the antecedents of user loyalty among sports fans. A survey conducted with 331 internet users reveals that user engagement is significantly influenced by factors such as content embeddedness and the empowerment provided by the programs. These factors positively affect user satisfaction, enhancing emotional involvement (referred to as "heart flow") and ultimately fostering user loyalty. Furthermore, the study confirms the positive impact of perceived ease of use and usefulness on user satisfaction and heart flow. Personality traits are also found to affect the continuity of sports content consumption. The findings underscore the importance of tailored public relations strategies in sports media to enhance user loyalty. Recommendations for sports broadcasters are provided to improve user engagement and loyalty by optimizing content delivery and interactivity, crucial for maintaining a competitive edge in the digital era.